2023
DOI: 10.3389/fnut.2023.1110750
|View full text |Cite
|
Sign up to set email alerts
|

Underutilized legumes: nutrient status and advanced breeding approaches for qualitative and quantitative enhancement

Abstract: Underutilized/orphan legumes provide food and nutritional security to resource-poor rural populations during periods of drought and extreme hunger, thus, saving millions of lives. The Leguminaceae, which is the third largest flowering plant family, has approximately 650 genera and 20,000 species and are distributed globally. There are various protein-rich accessible and edible legumes, such as soybean, cowpea, and others; nevertheless, their consumption rate is far higher than production, owing to ever-increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 161 publications
(165 reference statements)
0
4
0
Order By: Relevance
“…1,2 Protein content of some ULs such as sword bean (Canavalia gladiata) and fava bean (Vicia faba) has been found to be as high as 41−45%, comparable to animal protein. 3 Aside proteins, studies have also found the presence of beneficial phytochemicals and minerals. 4,5 Many legumes must, however, undergo some form of processing in order to make them suitable for consumption.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Protein content of some ULs such as sword bean (Canavalia gladiata) and fava bean (Vicia faba) has been found to be as high as 41−45%, comparable to animal protein. 3 Aside proteins, studies have also found the presence of beneficial phytochemicals and minerals. 4,5 Many legumes must, however, undergo some form of processing in order to make them suitable for consumption.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Underutilized legumes (ULs) have demonstrated the potential to contribute to food security, especially in the developing world. Many studies have suggested that they could adequately serve as alternative sources of dietary protein as animal sources tend to be expensive and unsustainable to produce. , Protein content of some ULs such as sword bean (Canavalia gladiata) and fava bean (Vicia faba) has been found to be as high as 41–45%, comparable to animal protein . Aside proteins, studies have also found the presence of beneficial phytochemicals and minerals. , Many legumes must, however, undergo some form of processing in order to make them suitable for consumption.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly a consequence of two phenomena: the growth of vegetarianism and the demand for protein not derived from wheat or other gluten-containing grains ( 30 , 31 ). However, the cultivation and consumption of legumes is still negligible as it is hindered by many nutritional, organoleptic and socio-economic barriers ( 32 ). It is, therefore, necessary to raise the awareness of the benefits of legumes from a nutritional and environmental point of view, emphasizing their potential role as a food, as well as an ingredient in traditional and non-traditional recipes and in the formulation of new products.…”
Section: Introductionmentioning
confidence: 99%
“…The term underutilized legumes refers to a diverse group of leguminous plants that have been historically overlooked or underused in mainstream agriculture and food systems, despite their potential nutritional, environmental, and socio-economic benefits [1]. These legumes encompass a wide range of species, many of which have been traditionally cultivated by indigenous communities or in specific regions but have received limited attention in terms of research, breeding, and commercialization compared to major crops like soybeans and common beans.…”
Section: Introductionmentioning
confidence: 99%